Soybean Cost-Return Budget in South Central Kansas - Ibendahl, Gregg; O'Brien, Daniel M.; Shoup, Douglas (My University, 2015)
This publication provides estimated cost and returns for forward farm planning for soybeans in south central Kansas.
MF2156_2015_04
Keywords: MF2156; Crops; Economics; MF